1986
DOI: 10.1073/pnas.83.21.8338
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus integration site in hepatocellular carcinoma at chromosome 17;18 translocation.

Abstract: Integrated hepatitis B virus (HBV) DNA is almost invariably found in hepatocellular carcinomas (HCC) which develop in HBV carriers. Integrated HBV DNAs from two single-integration HCCs (C3 and C4) have been cloned, and the cellular integration sites have been analyzed. Integrated HBV DNA of C3 is present in chromosome 6 and contains a nearly complete linear HBV genome. The HBV DNA integration in tumor C3 was not associated with major rearrangements of cellular DNA. In contrast, the integrated HBV DNA in C4 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(89 citation statements)
references
References 27 publications
3
85
0
1
Order By: Relevance
“…Double transgenic mice carrying both the SAP-IFN-y gene and the HBV genome will be a useful mouse model of viral hepatitis, because the release of HBsAg by liver cell damage may enhance the immune response to viral antigen, leading to liver cell injury. On the other hand, it is shown that chromosomal changes linked to HBV DNA integration occur frequently in host DNA of human HCC (25,26). Furthermore, it was shown that HBV DNA has recombinogenic functions in the hepatitis-related proliferative state (27) and that DNA rearrangement is involved in hepatocarcinogenesis (28).…”
Section: Discussionmentioning
confidence: 99%
“…Double transgenic mice carrying both the SAP-IFN-y gene and the HBV genome will be a useful mouse model of viral hepatitis, because the release of HBsAg by liver cell damage may enhance the immune response to viral antigen, leading to liver cell injury. On the other hand, it is shown that chromosomal changes linked to HBV DNA integration occur frequently in host DNA of human HCC (25,26). Furthermore, it was shown that HBV DNA has recombinogenic functions in the hepatitis-related proliferative state (27) and that DNA rearrangement is involved in hepatocarcinogenesis (28).…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen such structures, including unfinished ones (C6 and C1) that are too complex to analyze, are displayed in Figure 1. Because the major aim of this work is to obtain insights into general features of integrated HBV DNA, we also incorporated into the same figure 13 other reported cases (Dejean et al 1984;Koch et al 1984;Mizusawa et al 1985;Yaginuma et al 1985;Ziemer et al 1985;Hino et al 1986}.…”
Section: All the Integrated Virus Genomes Are Defectivementioning
confidence: 99%
“…Seven integrants have thus been studied and were assigned to chromosomes 3 (Dejean et al 1986), 6 (Hino et al 1986), 1 lp13-p14 (Rogler et al 1985), 11q22, 15q22-q23, 18q12 (Bowcock et al 1985, 17, and 18 (Hino et al 1986). Altogether, these results indicate that targets for HBV integration lie on at least 11 different chromosomes and suggest that HBV DNA does not show a strong preference for a particular chromosome for integration.…”
Section: Chromosome Assignment Of the Integrated Sitementioning
confidence: 99%
“…Despite of the fact that epidemiologic evidence indicates that the HBV is a major risk factor for the development of HCC (Robbins et al, 1994), the precise mechanisms of this association are unknown. The site of the cellular DNA at which the HBV integrates frequently undergoes rearrangement, resulting in a translocation, and deletion (Ogata et al,1990;Hino et al, 1996;Nakamura et al, 1998;Okabe et al, 2000). Furthermore, an allelic loss at 13q is significantly associated with an advanced tumor stage and a poor prognosis (Zondervan et al, 2000;Kusano et al, 2002;Wong et al, 2002).…”
Section: Discussionmentioning
confidence: 99%